Is drought protection possible without compromising flood protection? Estimating the potential dual-use benefit of small flood reservoirs in southern Germany - S. Q.-G. Ho; S. Q.-G. Ho; S. Q.-G. Ho; U. Ehret; U. Ehret (Hydrology and Earth System Sciences)
As climate change drives the intensification and increased frequency of hydrological extremes, the need to balance drought resilience and flood protection becomes critical for proper water resources management. Extreme droughts in the last decade in Germany have caused significant damages to ecosystems and human society, prompting renewed interest in sustainable water resources management. At the same time, protection from floods, such as the catastrophic flood in the Ahr Valley in 2021, weighs heavily on the public conscience. In the state of Baden-Württemberg in southwestern Germany alone, over 600 small (< 1 million m3) to medium-sized (1–10 million m3) reservoirs are currently operated for flood protection. In this study, we investigate the potential of different reservoirs to implement a dual flood–drought protection scheme that introduces a retention flow to store excess water for release in drought conditions, assuming that locations with more water available for storage will be better able to mitigate downstream streamflow drought. In total, 30 reservoirs in Baden-Württemberg were selected based on their size according to the German design standard DIN19700 (where small reservoirs have capacities of roughly 50 000–100 000 m3, medium have capacities of 100 000–1 000 000 m3, and large have capacities of more than 1 000 000 m3), their purpose (flood-only or multipurpose), and their relative water availability (expressed as the number of times the reservoir can be filled by the difference between the mean inflow and mean low flow). These reservoirs, despite their DIN19700 sizing categories, are small in the context of global reservoir studies. Daily target releases for drought protection are proposed based on the 70th percentile exceedance of modeled inflows from the calibrated LARSIM hydrological model. The retention flow is optimized to maximize penalty reduction in a scenario of perfect knowledge of flooding by using meteorological observations as artificial weather forecasts in LARSIM. The results of different retention flows are then evaluated based on their adherence to target releases and flood protection performance. Reservoirs were required to maintain the same level of flood protection under these modified rules. The optimized results were varied: some reservoirs can release up to 80 times their capacity with limited benefit for streamflow drought prevention; others can reduce streamflow drought conditions and water deficits by almost 95 % over a 24-year simulation period; and others have potential but are limited by either their capacity or flood protection constraints. There seems to be a trade-off between the relative water availability at the reservoir and the ability to alleviate drought conditions. We find that relative water availability at the reservoir has a strong relation to the amount of water a reservoir can release for drought protection, but it fails to summarily describe the reservoir's potential impact on drought conditions downstream.